Current Approaches to Wound Repair in Burns: How far Have we Come From Cover to Close? A Narrative Review - Šuca, Hubert; Čoma, Matúš; Tomšů, Júlia; Sabová, Jana; Zajíček, Robert; Brož, Antonín; Doubková, Martina; Novotný, Tomáš; Bačáková, Lucie; Jenčová, Věra; Kuželová Košťáková, Eva; Lukačín, Štefan; et al. (The Journal of surgical research, 2024)
Burn injuries are a significant global health concern, with more than 11 million people requiring medical intervention each year and approximately 180,000 deaths annually. Despite progress in health and social care, burn injuries continue to result in socioeconomic burdens for victims and their families. The management of severe burn injuries involves preventing and treating burn shock and promoting skin repair through a two-step procedure of covering and closing the wound. Currently, split-thickness/full-thickness skin autografts are the gold standard for permanent skin substitution. However, deep burns treated with split-thickness skin autografts may contract, leading to functional and appearance issues. Conversely, defects treated with full-thickness skin autografts often result in more satisfactory function and appearance. The development of tissue-engineered dermal templates has further expanded the scope of wound repair, providing scar reductive and regenerative properties that have extended their use to reconstructive surgical interventions. Although their interactions with the wound microenvironment are not fully understood, these templates have shown potential in local infection control. This narrative review discusses the current state of wound repair in burn injuries, focusing on the progress made from wound cover to wound closure and local infection control. Advancements in technology and therapies hold promise for improving the outcomes for burn injury patients. Understanding the underlying mechanisms of wound repair and tissue regeneration may provide new insights for developing more effective treatments in the future.
Keywords: transplantace kůže; jizva; Wound healing; Skin Transplantation; Burns; Wound Healing; Regeneration; Cicatrix; hojení ran; kůže; Wound dressing; Scar; Humans; lidé; popálení; Skin